Occupational Satisfaction of E-Rickshaw Drivers with Reference to Itahari-Nepal - Rai, Arjun (Dristikon: A Multidisciplinary Journal, 2019)
Seeing many electric rickshaws plying on plain rural and urban areas has become a common sight these days. Empirically, it can also be seen that many overseas returnees are taking up the occupation as an e-rickshaw driver as a means of financing their family needs. In the backdrop of this context, this research paper attempts to explore the challenge & opportunities associated with their occupation, their intention to switch from their current occupation, satisfaction of e-rickshaw drivers of Itahari, Nepal. This study used a structured questionnaire to collect primary data from 95 electric rickshaw drivers of Itahari. For data analysis, the researcher used Statistical Package for Social Science- 20. Descriptive and inferential statistical tools were used in the study. The findings of the study shows that, on average the e-rickshaw drivers are satisfied with their current occupation, majority of them do not have intention to switch occupation. The commonest problems faced by them are “the condition of the road” and “traffic problem”.